Diferencias Transculturales en la Manifestación del Bullying en Estudiantes de Escuela Secundaria - Carolina Vega; Yeni Medina; Marjorie E. Ortega; Hannia Cabezas; Leonor I. Lega; Maria Teresa Paredes (Revista Latinoamericana en Ciencias Sociales, Niñez y Juventud, 2011)
A matched group design by age and grade level compared the results of two previous single experimentsdone in two different countries, Colombia and Costa Rica, on the phenomenon of bullying. The purpose was to identify theaggresor’s behavior to make and compare their profile and the explore the variable of gender in this issue. The study consistedof 824 male and female participants, ages of 12 to 16, grades 6th to 8th,, anonimously answered the Paredes, Lega, VernonQuestionary for Bullying Detection. The results of a two-way MANOVA showed that there were main effects in genderand country, and a significant gender and country interaction.